The writer’s notebook and postmodern literature: points of convergence - Ефимова, Светлана (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
This article begins with a brief characterization of the writer’s notebook as a special text type. Then the article analyzes structural and compositional features that notebooks of the 19th and 20th centuries have in common with postmodernist prose. These features include: a) fragmentary narration; chaotic composition; many syntactic and semantic ellipses; b) the absence of one main idea and an important role of chance in the creative process; c) an opportunity to start reading a text from any of its parts, even from the end; d) a great number of intertextual links; similarity to hypertext; e) no stylistic and thematic limitations, etc. There are three possible explanations of these points of convergence: a psychological one, a linguistic one and a historical-literary one.